Modeling default dependence with threshold models - Ludger Overbeck; Wolfgang M. Schmidt (Hochschule für Bankwirtschaft (HfB), 2003)
We investigate the problem of modeling defaults of dependent credits. In the framework of the class of structural default models we study threshold models where for each credit the underling ability-to-pay process is a transformation of a Wiener processes. We propose a model for dependent defaults based on correlated Wiener processes whose time scales are suitably transformed in order to calibrate the model to given marginal default distributions for each underlying credit. At the same time the model allows for a straightforward analytic calibration to dependency information in the form of joint default probabilities.
urn:nbn:de:101:1-2008071857
Keywords: G12; 330; Credit default; credit derivative; default dependence; structural form models; threshold model